Le dilemme de Buridan : Une histoire de la traduction belge est-elle possible ? - D'hulst, Lieven (chronotopos – A Journal of Translation History, 2019)
Whenever they attempt to cover longer periods, translation histories, like national and comparative literary histories, face the paradox of Buridan’s ass: should they limit the scope to intranslations in the national language only or should they open up to extranslations of national works in other languages? The first option being commonly taken, translation histories tend to follow the restrictive path of national literary histories. However, when dealing with multilingual literatures, like Belgian literature, such a dependence yields more problematic effects: since histories focus on one language only, translation histories simply ignore the intensive translation exchanges between the two major national languages, as well as the role played by Belgian translations in the international circulation of literature. This contribution aims at disentangling the various issues associated with translation in Belgium and proposes some solutions for its analysis, including an integrated view of qualitative and quantitative approaches.